Exploring Guests’ Satisfaction and Dissatisfaction with Homestay Experiences: A Netnographic Study of a Rural Tourism Destination in Vietnam - Brian Garrod (International Journal of Hospitality & Tourism Administration, 2024)
Few studies have used online reviews to gain useful insights into homestay guests’ satisfaction. This study responds to demands from the existing literature on homestay tourism in a rural destination context to identify the factors that contribute to tourists’ satisfaction and dissatisfaction by examining homestay experiences in Vietnam’s Ben Tre province. User-generated content on Booking.com was analyzed using a netnographic approach. The data comprised 656 online posts. The findings suggest that guests achieve satisfaction from host families’ attitudes and language abilities, high-quality facilities in the bedrooms and grounds, authentic cuisine, a peaceful location, the availability of complementary services, and affordable prices. The findings contradict studies suggesting that homestay guests may seek familiarity, and this was largely not evident in terms of tourist food consumption while at the destination. In addition, the findings challenge studies indicating that prices have a strong influence on tourists’ satisfaction with homestay tourism.